Tailoring Light–Matter Interactions in Overcoupled Resonator for Biomolecule Recognition and Detection - Li, Dongxiao; Zhou, Hong; Ren, Zhihao; Xu, Cheng; Lee, Chengkuo (Nano-Micro Letters, 2024)
Plasmonic nanoantennas provide unique opportunities for precise control of light–matter coupling in surface-enhanced infrared absorption (SEIRA) spectroscopy, but most of the resonant systems realized so far suffer from the obstacles of low sensitivity, narrow bandwidth, and asymmetric Fano resonance perturbations. Here, we demonstrated an overcoupled resonator with a high plasmon-molecule coupling coefficient (μ) (OC-Hμ resonator) by precisely controlling the radiation loss channel, the resonator-oscillator coupling channel, and the frequency detuning channel. We observed a strong dependence of the sensing performance on the coupling state, and demonstrated that OC-Hμ resonator has excellent sensing properties of ultra-sensitive (7.25% nm−1), ultra-broadband (3–10 μm), and immune asymmetric Fano lineshapes. These characteristics represent a breakthrough in SEIRA technology and lay the foundation for specific recognition of biomolecules, trace detection, and protein secondary structure analysis using a single array (array size is 100 × 100 µm2). In addition, with the assistance of machine learning, mixture classification, concentration prediction and spectral reconstruction were achieved with the highest accuracy of 100%. Finally, we demonstrated the potential of OC-Hμ resonator for SARS-CoV-2 detection. These findings will promote the wider application of SEIRA technology, while providing new ideas for other enhanced spectroscopy technologies, quantum photonics and studying light–matter interactions. Highlights: 1 Proposed a new paradigm for nanoantenna design using coupled-mode theory. 2 Designed an OC-Hµ resonator with excellent sensing performance. 3 Using OC-Hµ resonators for biomolecule recognition and detection.